Etnografía sin remordimientos - Wolcott, Harry F. (Revista de Antropología Social, 2007)
Professor Wolcott looks back over his studies in anthropology and education to answer the question, “Where do our studies go and what do they do there?”. In this writing he is particularly concerned with regrets –things that he wishes he had done differently or that did not turn out as he hoped and planned–. His advice to future ethnographers is to keep “regrets” in mind as a personal responsibility in deciding how much to reveal about the people with whom one works. He reminds us that we can always add information later, but it is not possible to retract errors of judgment we may make at the time.